Immobilization of Fe-Doped Ni2P Particles Within Biomass Agarose-Derived Porous N,P-Carbon Nanosheets for Efficient Bifunctional Oxygen Electrocatalysis - Xiao, Yifan; Deng, Sihui; Li, Meng; Zhou, Qixing; Xu, Libang; Zhang, Huaifang; Sun, Dongmei; Tang, Yawen (Frontiers in Chemistry, 2019)
A feasible and green sol-gel method is proposed to fabricate well-distributed Fe-Ni2P particles immobilized in N, P-codoped porous carbon nanosheets (denoted as Fe-Ni2P@N,P-CNSs) by using biomass agarose as carbon source, ethylenediamine tetra (methylenephosphonic acid) (EDTMPA) as both the N and P sources. The incorporation of Fe atom in Ni2P is essential to enhance catalytically active sites, and the N,P-codoped porous carbon endows Fe-Ni2P@N,P-CNSs with a high specific surface area, graphitization degree and electrical conductivity. Benefiting from the composition and structure advantages, the as-synthesized Fe-Ni2P@N,P-CNSs manifests the satisfied oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) performance in alkaline solution, including the low overpotential, small Tafel slope and long-term durability, which obviously outperform the single component counterparts (Fe-free Ni12P5/Ni2P2O7@N,P-CNSs and CNSs) and are even comparable to Pt/C and RuO2 catalysts. The present work would broaden the picture for the exploration of efficient bifunctional oxygen electrocatalysts with earth abundant biomass as carbon source to substitute noble metals for the renewable energy conversion/storage.